2017
DOI: 10.1111/nhs.12358
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplant patients’ transition to adulthood: Patient and parent experiences

Abstract: This qualitative research study describes the experiences of child and adolescent liver transplant recipients and their parents during the patients' transition to adulthood. Data were collected from pediatric liver transplant recipients and their parents during individual interviews, and these were later analyzed using conventional content analysis. Seven main themes emerged: coping, self-management, body image, social relationships, academic life, work life, and live donors. Study results revealed that the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…37 For adolescents with chronic illness, mental health concerns, and reduced quality of life may be further amplified. 38,39 This finding is consistent in studies reporting psychosocial concerns in young people post-liver transplantation 40 and mental health issues such as anxiety and depression. 41 Transition clinics also enabled the identification of risk and adherence issues in addition to psychosocial, mental health, and school issues.…”
Section: Discussionsupporting
confidence: 79%
“…37 For adolescents with chronic illness, mental health concerns, and reduced quality of life may be further amplified. 38,39 This finding is consistent in studies reporting psychosocial concerns in young people post-liver transplantation 40 and mental health issues such as anxiety and depression. 41 Transition clinics also enabled the identification of risk and adherence issues in addition to psychosocial, mental health, and school issues.…”
Section: Discussionsupporting
confidence: 79%
“…Mixed findings regarding psychological functioning were noted in 3 studies 21,23,38 . Heart transplant recipients in 1 study did not report overall elevated levels of depression or anger, though they reported high anxiety; however, scores were not compared to a control group 23 .…”
Section: Resultsmentioning
confidence: 93%
“…Eighteen studies reported on educational and occupational status of SOT recipients 13–15,21,22,24,28,29,33–42 . Studies found that the majority of SOT recipients (ranging from 74% to 100%) had completed high school, and 22% to 65% had engaged in post‐secondary study (e.g., vocational training, college, university).…”
Section: Resultsmentioning
confidence: 99%
“…• The transition phase is associated with complications and experiences of exacerbations in the adolescent's condition [12][13][14] and an increased number of noattendance at outpatient clinical visits in adult care [15,16]. • The transition phase has also been shown to significantly impact parents, including an increased risk of developing anxiety and stress [17][18][19][20] and a general concern and sense of uncertainty about their child's transfer to adult care [21,22].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…The transition phase has also been shown to significantly impact parents, including an increased risk of developing anxiety and stress [ 17 20 ] and a general concern and sense of uncertainty about their child’s transfer to adult care [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%